New biomaterial based on cotton with incorporated biomolecules - Gomes, Ana P. (2014)
The aim of this study was to investigate a method of embedding l-cysteine (l-cys), an antimicrobial agent, between layers of chitosan (CH) and sodium alginate (ALG) onto cotton samples obtained via a layer-by-layer electrostatic deposition technique via several embedding methods. The results show that the best way to incorporate l-cys into the layers was the one that used the property of gelling ALG. To monitor the l-cys embedding into the CH/ALG multilayer film, different methods were used: energy-dispersive X-ray spectrometry analysis to assess the presence of sulfur on the sample, Ellman's reagent method to analyze l-cys release from the sample, and attenuated total reflectance (ATR) Fourier transform infrared spectroscopy (FTIR) to compare the ATR–FTIR spectra of the pure l-cys and l-cys embedded in the CH/ALG multilayer film to study the interaction between the l-cys and the CH/ALG multilayer films. Functionalized CH/ALG cotton samples were also investigated for their antibacterial properties toward Staphylococcus aureus andKlebsiella pneumonia with the Japanese Industrial Standard method JIS L 1902:2002, and the results show an enhancement of the antibacterial effect due to the presence of l-cys.